Impaired Nicotinamide Adenine Dinucleotide Biosynthesis in the Kidney of Chronic Kidney Disease - Liu, Xinhui; Luo, Denggui; Huang, Shiying; Liu, Siqi; Zhang, Bing; Wang, Fochang; Lu, Jiandong; Chen, Jianping; Li, Shunmin (Frontiers in Physiology, 2021)
Chronic kidney disease (CKD) is a global public health problem with high morbidity and mortality. Decreased nicotinamide adenine dinucleotide (NAD+) levels were found to be associated with aging, cancer, and neurodegenerative and metabolic disorders. However, the alteration of renal NAD+ levels and biosynthesis pathways in CKD is less known. In the present study, we aimed to evaluate renal NAD+ levels and tested the expression of key enzymes in three NAD+ biosynthesis pathways in two different types of CKD rat model. CKD rat models were established by 5/6 nephrectomy (5/6 Nx) and feeding with adenine-containing feed, respectively. Renal function was assessed by serum creatinine (Scr) and blood urea nitrogen (BUN). Renal pathology was evaluated by periodic acid-Schiff (PAS) and Masson’s trichrome staining. The expression of key enzymes in three NAD+ biosynthesis pathways was determined and quantified by Western blot analysis. The results showed CKD rat models were successfully established as evidenced by increased Scr and BUN levels, upregulation of neutrophil gelatinase-associated lipocalin (NGAL), glomerular hypertrophy, and renal fibrosis. Renal NAD+ and NADH content were both declined in two CKD rat models, and NAD+ levels were negatively correlated with Scr and BUN levels in CKD rats. Three key enzymes involved in NAD+ biosynthesis were significantly downregulated in the kidney of both of the two CKD models. They were quinolinate phosphoribosyltransferase (QPRT) in the de novo pathway, nicotinamide mononucleotide adenylyltransferase 1 (NMNAT1), and NMNAT3 in the salvage pathway. Moreover, the expression of NAD+-consuming enzymes sirtuin 3 (SIRT3) and CD38 decreased significantly in CKD rats. In conclusion, NAD+ biosynthesis was significantly impaired in CKD, which may attribute to downregulation of QPRT and NMNAT 1/3.